EFEKTIVITAS METODE P2R UNTUK MENINGKATKAN KECEPATAN EFEKTIF MEMBACA (KEM) MAHASISWA CALON GURU BAHASA INDONESIA - Nurmina, Nurmina (Jurnal Penelitian Pendidikan, 2015)
Reading is one of language skill which is not less important compared with others language skill such as scrutinizing, speaking, and writing. In this era which technology is flaring and developing rapidly, the students are prefer to play facebook, twitter, chatting, and many more than read a journal or articles. This phenomenon shows that the interest to read among students is needed to be increased. One of the way that can be taken is by having skills to read quickly or is known by scanning with P2R method. The P2R method itself is one of method or strategy that can be used to increase reading skill. The P2R method consists of stages pra-peninjauan, membaca, dan meninjau that commonly used by the most of quick reader / scanner and efficient. This research is done to obtain data about the effective reading speed of student as Indonesian language teacher candidate and the effort of its increasing through the P2R method. The population of this research is all students on program of study Indonesian language and literature education and also area of Almuslim University as much 149 students. The sample of this research is 30% of the total population or as much 45 strudents of Indonesia Language teacher candidate of Almuslim University who are taken randomly. The type of research is experimental research (true experimental) and quantitative approach with the model of research is pretest-post test control group model. The result of research shows that the P2R method is effective to be implemented to increase the effective reading speed of students as Indonesian language teacher candidate. FKIP is obtained by researcher. The posttest result shows that there was an increasing of KEM learning outcomes meanwhile the observation result was seems that in the learning with P2R model, the students were very enthusiasm, more active, also more motivated in attending the learning. Besides that, the result of questionnaires also shows that the P2R method obtained the positive responses from students. The students felt that P2R method was very helpful and made them easy in reading. Based on the test result and observation and questionnaires, it can be concluded that P2R method is effective to increase the effective speed reading of students as Indonesian Language teacher candidate, FKIP of Almuslim University learning year 2015/2016.